Hyperglycemia as a prognostic factor of mortality in patients with SARS-CoV-2 - Camacho-Saavedra, Luis Arturo (2020)
A research was made on whether hyperglycemia is a predictor of mortality in patients infected with SARS-Cov 2. Articles were searched in the PubMed and Google Scholar databases until July 30, 2020. The keywords were used: “Hyperglycemia”, “Serious Acute Respiratory Syndrome”, “Viral Pneumonia”, “Virosis”, “Coronavirus Infections”, “incubation period”, “transmission”, “clinical characteristics”, “physiopathology”, “hyperglycemia”, with the interposition of the Boolean operator” and “”. In addition, we access the scientific literature and recommendations currently available on WHO websites and the U.S. Centers for Disease Control and Prevention (CDC). Patients infected with SARS-CoV-2 and hyperglycemia (blood glucose >180 mg /dL) had higher mortality compared to patients with controlled blood glucose. Acute or chronic hyperglycemia and, moreover, when it  remains uncontrolled is associated with increased severity and mortality in patients infected with SARS-CoV-2.